Morphometric Analysis of the Fawn Roundleaf Bat, Hipposideros cervinus (Gould, 1854) (Chiroptera: Hipposideridae), from Several Populations in Sarawak - SAZALI, SITI N.; JUARY, JOSEPHINE (Tropical Natural History, 2012)
A morphometric analysis of three different populations of Hipposideros cervinus in Sarawak, Malaysian Borneo, was performed using voucher specimens deposited in the UNIMAS Zoological Museum that had been collected from the three different geographical regions (populations) of Kubah National Park, Tubau and Niah National Park. A total of 27 characters, derived from external, cranial and dental measurements, were used. The measurements were recorded and analyzed using Discriminant Function Analysis (DFA) with the SPSS Version 18.0 software. The highest character loading for Functions 1 and 2 were the canine molar length or maxillary tooth row length (C1M3L) and the ear length (EL), with standardized canonical discriminant function coefficient values of 0.680 and 0.711, respectively. These two characters are identified as the best predictors to distinguish the three populations based on their morphological measurements. Accordingly, it is proposed that the different types of habitats, foraging behavior and food availability are among the factors that could lead to morphological variations among H. cervinus populations.